Electrochemical treatment of real petrochemical effluent current density effect and toxicological tests - de Melo, Jaqueline Ferreira (Water science and technology : a journal of the International Association on Water Pollution Research, 2020)
This work aims to investigate the electrochemical treatment of petrochemical industry effluents (from the northwest region of Brazil) mediated by active chlorine species electrogenerated at ruthenium-titanium oxide supported in titanium (Ti/Ru0.3Ti0.7O2) and boron doped diamond (BDD) anodes by applying 15 and 45 mA cm-2. Chemical oxygen demand (COD) determinations and toxicity analyses were carried out in order to evaluate the process extension as well as the possible reuse of the wastewater after treatment. Toxicity was evaluated by assessing the inhibition of lettuce (Lactuca sativa) stem growth, seed germination, and the production of nitrite (NO-2) and nitrate (NO-3) species. Results clearly showed that the best COD reduction performances were reached at the BDD anode, achieving almost 100% of removal in a short time. Degradation of nitrogen-organic compounds generated NO-2 and NO-3 which act as nutrients for lettuce. Toxicity results also indicated that the electrogenerated active chlorine species are persistent in the effluent after the treatment, avoiding the stem growth, and consequently affecting the germination